Driving and use of the mobile phone: a study among 18 to 24-year-old - Gaymard, Sandrine; Besson, Thomas; Bessin, Mathieu; Egido, Angel; Coutelle, Nolwen; Eberhardt, Rose; Hennequin, Noémie (Advances in Social Sciences Research Journal, 2019)
While we know that using the telephone when driving increases the risk of accidents and that 18 to 24 year-olds are a fringe of the population that is particularly affected by fatal accidents on the road, we lack information concerning the use of the mobile phone in this age group. This study carried out with 208 young drivers aims to gather data, analyses their behavior at the wheel with the mobile plus their beliefs and awareness of risk. Three contexts are focused on: stopping at the red light, driving during the rush hour and highways. The findings highlight the importance of messaging and the influence of the context on the use of the mobile. We observe an inverse effect between the speed and messaging. While young people declare they are aware of certain risks, it concerns more the risks penalties and accordingly they appear to be impervious to road safety campaigns concerning the mobile phone behind the wheel. On this subject few major differences are to be found between male and female drivers and between very young and young drivers. The use of the mobile while driving among 18 to 24-year-olds therefore presents universal characteristics of use from moment or the driver (male or female) is a little more experimented.